Pengaruh Persentase Pati Jagung Pada Komposit LDPE Terhadap Kekuatan Bending Dan Biodegradasi - Mustholih, Imam; Kencanawati, Cok Istri Putri Kusuma; Priambadi, I Gusti Ngurah (Teknik Desain Mekanika, 2022)
Abstract Plastic is a material that we often encounter in the surrounding environment such as homes, schools, workplaces, but plastic will often become a hygiene problem because of the length of time it takes to decompose independently by nature. The use of composites aims to regulate when the composite can decompose with the help of natural materials such as corn starch and can determine the strength and efficiency of this composite.This study used Low Density Polyethylene plastic seeds as a matrix and corn starch as a filler, LDPE heating was carried out at 115ºC, LDPE and corn starch composites used volume fraction 95% LDPE: 5% corn starch 90% LDPE: 10% corn starch 85% LDPE : 15% corn starch implanted using an aluminum mold with reference to ASTM D790-03 Degradation testing was carried out by cutting the composite to reach a size of 1cmx1cmx1cm and would be planted in the soil for 30 days. Bending test data showed an increase in strength in the 15% corn starch fraction: 85% LDPE with a stress value of 19.283 MPa, in the degradation test the largest decrease occurred in the 15%: 85% fraction of 2.96%. Microstructural testing showed a better and more even distribution of corn starch. From the test results obtained are composites with a volume fraction of 15% corn starch: 85% LDPE has an increase compared to other volume fractions Keywords: corn starch, low density polyethylene, degradation, bending strength